Respuesta :

Answer:

1. -y

3. 9a-7

5. 14x-2

7. 7d-6

Step-by-step explanation:

1. 8y-9y=-y

3. 8a-6+a-1

=(8a+a)-(6+1)

=9a-7

5. -x-2+15x

=(-x+15x)-2

=14x-2

7. 8d-4-d-2

=(8d-d)-(4+2)

=7d-6

TehGOD

Answer:

1. -x

3. 9a-7

5. 14x-2

7. 7d-6

Step-by-step explanation:

To do the first one you would just subtract 8 by 9 which is -1 so you would get -x as 1.

To do the third one would would just move the numbers around so you get 8a+a-6-1 and when you simplify you get 9a-7.

To do the fifth one you just have to move the numbers so you get -x+15x-2 and when you simplify you get 14x-2

To do the seventh one you just have to move the numbers so you get 8d-d-4-2 and when you simplify you get 7d-6.

ACCESS MORE